Subclasses of Analytic Functions with Negative Coefficients Involving q-Derivative Operator - Andy Liew Pik Hern; Aini Janteng; Rashidah Omar (Science and Technology Indonesia, 2022)
Let A denote the class of functions f which are analytic in the open unit disk U. The subclass of A consisting of univalent functions is denoted by M. In this paper, we also consider a subclass of M which is denoted by V, consisting of functions with negative coefficients. In addition, this paper also studies the q-derivative operator. By combining the ideas, this paper introduced three subclasses of A with negative coefficients involving q-derivative. Furthermore, the coefficient estimates, growth results and extreme points were obtained for all of these classes.